2021
DOI: 10.1016/j.lfs.2020.118977
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone mediates cardioprotection against postinfarction remodeling and dysfunction through the IGF-1/PI3K/AKT signaling pathway

Abstract: BackgroundSevere cardiovascular diseases, such as myocardial infarction or heart failure, can alter thyroid hormone (TH) secretion and peripheral conversion, leading to low triiodothyronine (T3) syndrome. Accumulating evidence suggests that TH has protective properties against cardiovascular diseases and that treatment with TH can effectively reduce myocardial damage after myocardial infarction (MI). However, the potential mechanisms are not clear. This study was designed to investigate the effect of T3 pretre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…All six genes have previously been reported in the context of radiation or DNA damage response and fall into three main biological roles: cell cycle arrest, hemoglobin metabolism, and inflammatory response (Table 1 ). The prior relevant literature on Cdkn1a [ 53 , 54 ], Gdf15 [ 55 , 56 ], Ckap2 [ 57 , 58 ], Alas2 [ 59 , 60 ], Aplnr [ 61 , 62 ] and Cx3cr1 [ 63 , 64 ] are listed in Table 1 . We validated the expression of the most significantly upregulated and downregulated mRNAs in our data using RT-qPCR (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…All six genes have previously been reported in the context of radiation or DNA damage response and fall into three main biological roles: cell cycle arrest, hemoglobin metabolism, and inflammatory response (Table 1 ). The prior relevant literature on Cdkn1a [ 53 , 54 ], Gdf15 [ 55 , 56 ], Ckap2 [ 57 , 58 ], Alas2 [ 59 , 60 ], Aplnr [ 61 , 62 ] and Cx3cr1 [ 63 , 64 ] are listed in Table 1 . We validated the expression of the most significantly upregulated and downregulated mRNAs in our data using RT-qPCR (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…When the brain is seriously injured, intracranial hemorrhage induces an increase in intracranial pressure, ischemia, and hypoxia in brain tissue. At the same time, the activities of 5-deiodinase and nerve cell enzymes are greatly reduced, resulting in a decrease in the number of TT3 and the intake of TT4 [ 11 , 12 ]. At the same time, a severe craniocerebral injury may also induce the occurrence of stress diseases, thus, inhibiting the secretion of TSH and reducing the level of TSH [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our pathway enrichment results, previous studies have reported that regulation of oxidative stress-related gene expression was functionally associated with PI3K/AKT signaling, which is a key profibrotic element in various tissues and was reported to be capable of activating atrial fibroblasts to differentiate into myofibroblasts [ 39 ]. Several experimental studies have sought targets to inhibit atrial remodeling by affecting oxidative stress, inflammation, and the PI3K/Akt signaling pathway [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%